1995
DOI: 10.1111/j.1439-0434.1995.tb00263.x
|View full text |Cite
|
Sign up to set email alerts
|

Peroxidase Activity and Isoperoxidase Pattern in Tobacco Leaves Infected with Tobacco Necrosis Virus and Other Viruses Inducing Necrotic and Non‐Necrotic Alterations

Abstract: The level of peroxidase activity was greatly enhanced in tobacco leaves infected by tobacco necrosis virus (TNV) and other viruses which induce neerotie symptoms (TMV, ToM V and PVY^). The intensity was related to the age of the leaves infected: absent or negligible in mature leaves and very pronounced in young growing infected leaves. On the eontrary, changes in peroxidase activity were negligible when the infection was provoked by viruses which do not produce necrotic reactions (TMV and PVY°). Analysis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 35 publications
1
13
0
1
Order By: Relevance
“…A lot of studies confirmed the increase of POX activity during or after pathogen attack [10,45,50,51]. The changes in POX activity and their distribution indicate three levels of response: (a) non-specific changes associated with the inoculation; (b) changes associated with a general defence response; (c) responses that have relevance to the development of HR.…”
Section: Discussionmentioning
confidence: 84%
“…A lot of studies confirmed the increase of POX activity during or after pathogen attack [10,45,50,51]. The changes in POX activity and their distribution indicate three levels of response: (a) non-specific changes associated with the inoculation; (b) changes associated with a general defence response; (c) responses that have relevance to the development of HR.…”
Section: Discussionmentioning
confidence: 84%
“…cellulase preparations. Biochemical indicators of localized and systemic defense responses were investigated, such as peroxidases (Montalbini et al, 1995;Martinez et al, 1996) and chitinases (Sahai and Manocha, 1993). Treatment with A-cell.20 and A-cell.50 caused a weaker induction of peroxidase activity than NA-cell.20 or Nacell.50 infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…Lignin synthesis, cross-linking cell wall polysaccharides, and phenol oxidation have been proposed among the physiological roles postulated for peroxidases (Lagrimini et al, 1993). In virus-infected plants enhanced peroxidase activity has been found associated with hypersensitive response and systemic-acquired resistance (SAR) (Montalbini et al, 1995).…”
Section: Introductionmentioning
confidence: 99%